Inflammatory Markers Are Positively Associated with Serum trans-Fatty Acids in an Adult American Population - Mohsen Mazidi; Hong-kai Gao; Andre Pascal Kengne (Journal of Nutrition and Metabolism)
Background and Aim. The relationship between serum trans-fatty acids (TFAs) and systemic inflammation markers is unclear. We investigated the association of serum TFAs with high sensitivity C-reactive protein (hs-CRP) and fibrinogen in adult Americans. Methods. The 1999 to 2000 National Health and Nutrition Examination Survey (NHANES) participants with measured data on hs-CRP and fibrinogen were included. TFAs were measured via capillary gas chromatography and mass spectrometry using negative chemical ionization. Analysis of covariance and multivariable-adjusted linear regression models were used to investigate the associations between these parameters, accounting for the survey design. Results. Of the 5446 eligible participants, 46.8% (n=2550) were men. The mean age was 47.1 years overall: 47.8 years in men and 46.5 years in women (p=0.085). After adjustment for age and sex, mean serum TFAs rose with the increasing quarters of hs-CRP and fibrinogen (both p<0.001). In linear regression models adjusted for age, sex, race, education, marital status, body mass index, and smoking, serum TFAs were an independent predictor of plasma hs-CRP and fibrinogen levels. Conclusion. A high level of TFAs appears to be a contributor to an unfavourable inflammatory profile. Because serum TFAs concentrations are affected by dietary TFA intake, these data suggest a possible contribution of TFAs intake modulation in the prevention of inflammation-related chronic diseases.